Total carbon, total organic carbon, and total inorganic carbon (solid-phase discrete samples) from IODP Hole 389-M0096F - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
Total carbon (TC), total organic carbon (TOC), and total inorganic carbon (TIC) content from solid-phase discrete samples from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). The offshore phase of this expedition took place between 2023-08-31 and 2023-10-31 onboard multipurpose vessel MMA Valour sailing from and to Barbers Point Harbor, Hawai extquotesinglei, USA, followed by the onshore phase from 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. During the onshore phase a set of solid-phase samples were taken from the work halves of core sections, with a volume of approx. 10 cubic centimeters each, were taken with the purpose to be later on split into aliquots for the following three analyses: X-ray diffraction, carbon and X-ray fluorescence. Bulk samples were subsequently freeze-dried, ground and homogenized to a fine powder (<20 μm particle size) by ECORD Science Operator staff using a pestle and an agate mortar or a ball mill. Sample aliquots of approx. 100 mg (TC) and 1 g (TOC) were processed through a CS744 LECO carbon-sulfur analyzer to obtain the respective concentrations. TIC was calculated as the difference between TC and TOC. For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025